Pengaruh Kapasitas Kepala Desa Terhadap Pengelolaan Dana Desa di Desa Sidomulyo Kecamatan Banjarejo Kabupaten Blora - Suyatman; Annis Nurfitriana Nihayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The capacity of the village head plays a central role in determining the effectiveness of village fund management. As the highest leader at the village level, the village head is expected to be able to carry out government functions effectively, including planning, implementing, and accounting for the use of village funds in a transparent and accountable manner. In the context of Sidomulyo Village, Banjarejo District, the village head's ability to understand regulations, organize village officials, and foster community participation are key factors in creating effective village fund governance. Using a descriptive qualitative approach, this study reveals that the village head's capacity, encompassing knowledge, skills, and commitment, directly contributes to the success of each stage of village fund management. Planning is carried out in a participatory manner through village deliberations, program implementation is aligned with the community's real needs, and reporting is conducted openly through various village information media. Active community participation and a strong culture of mutual cooperation (gotong royong) also strengthen the social oversight system for fund use. These results confirm that the success of village development depends heavily on the synergy between strong village leadership and active community involvement.